Photo-crosslinkable PEG-based microribbons for forming 3D macroporous scaffolds with decoupled niche properties - Han, Li-Hsin (Advanced materials (Deerfield Beach, Fla.), 2014)
© 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.